Navigating the Shadows: The Social Impacts of Parental Incarceration on Children and Policy Recommendations for Global Change - Stella, Michael-Makri (European Journal of Social Science Education and Research, 2024)
Parental incarceration affects millions of children worldwide, imposing severe emotional, social, and psychological challenges that are often unaddressed by current systems. This article examines how parental incarceration contributes to stigma, social isolation, disrupted family dynamics, and systemic inequality. Utilizing frameworks such as Labeling Theory and Attachment Theory, it analyzes the compounded impact on children, with specific attention to gender and cultural differences. For example, children in punitive systems like those in the United States face heightened stigma and reduced family connections, whereas rehabilitative models in Norway and Sweden demonstrate better outcomes by emphasizing family ties and social support. Gender-specific responses and the unique struggles of marginalized groups are explored, underscoring the need for trauma-informed, culturally sensitive interventions. The article advocates for reforms across justice, education, and social systems to prioritize family-centered policies and community support. Such measures, as evidenced in programs like FamilyWorks in the U.S. and Pillars in New Zealand, can mitigate negative effects, promote resilience, and improve life trajectories for children affected by parental incarceration.